PENGARUH METODE CREATIVE PROBLEM SOLVING (CPS) MODEL TREEFINGER TERHADAP HASIL BELAJAR PERAKITAN KOMPUTER PADA SISWA KELAS X TEKNIK KOMPUTER JARINGAN SMK N 1 RAO SELATAN - Hakiki, Muhammad; Fadli, Radinal (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2020)
This research was quantitative research that used a true experiment research approach and a posttest-only control as the research design. This research conducted in SMK 1 Rao Selatan. The population in this research was the grade X students of computer engineering and network major in SMK 1 Rao Selatan. The technique sampling in this research was a total sampling or also called as a population research. In determining the experiment class and control class, the researcher used rolls of paper. Grade X of TKJ 2 elected as experiment class and grade X TKJ 1 elected as control class. The result of this research were average the students learning outcomes in experiment class was about 80,90 while in control class was about 74,84. From analysis test showed normal and homogeny data. The test result on the level significance a0,05 (the level of confidence 95%) obtained score thitung=3,498 and ttabel=2,000 so obtained Thitung>Ttabel (3,498>2,000). Therefore, Ho rejected and Ha accepted in this research. So, the conclusion was there a significant influence in Creative Problem solving (CPS) learning method with Treefingermodel toward learning outcomes of assembly computer of grade X students in program computer network engineering SMK 1 Rao Selatan.